An unusual case of interstitial pregnancy: a case report - Sebastian, Nikhil; Radhakrishnan, Abhishek; Murugesan, Vennila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Ectopic pregnancy (EP) has been found to be a common cause of morbidity, and on occasion, mortality among women in the reproductive age groups. The incidence of EP is 1-2% of all pregnancies. 93-97% of EP are tubal with the interstitial type consisting only 3-4%. A 31-year-old female patient with primary infertility underwent IVF (In Vitro Fertilization). Pregnancy was confirmed by βHCG (beta human chorionic gonadotropin). Her ultrasonography reported a mass in the right cornual region. The uterine cavity was empty. Laparoscopy was performed followed by resection of the right cornua with tubes. Histopathology report confirmed the diagnosis of Interstitial Pregnancy (IP). The patient had an uneventful post-operative period and was discharged the next day. EP is a common complication seen in cases undergoing IVF, and IP is a rare form of EP. Hence, early diagnosis and prompt intervention is required to avoid a potentially life-threatening situation.